Aspects on Applying and Operating Campus Networks in Agriculture - Hecker, Andreas; Striller, Benjamin; Boye, Fredrik; Franchi, Norman; Freytag, Hagen (VDI Verlag GMBH, 2022)
Private (campus) networks with a cloud-based architecture provide a solution for automated data communication in agriculture and effective management of farm businesses, making it possible to achieve increasing economic and ecological targets. The experimental test field LANDNETZ builds and tests mobile private networks, which, for the first time, have been designed for agricultural applications and farm environments [1]. The goal of LANDNETZ is to develop networking solutions that operate on the basis of use cases (application-specific operation) and to investigate operational aspects of private campus networks and their potential for improvements. In this paper, the authors introduce recent examples of agricultural applications, outline their requirements for a campus network solution, and present necessary aspects of operating a campus network.
CRIS-Team Scopus Importer:2024-12-16